Mortality from Cardiopulmonary Diseases in Brazil: Data from 2023–2024 (CIPEEX, 2025)
This study aimed to analyze mortality fromcardiopulmonary diseases in Brazil, with emphasis on theState of Goiás and the municipalities of Itapuranga, Uruana, and Uruíta, between the years 2022 and 2024. Cardiopulmonary diseases, such as Chronic ObstructivePulmonary Disease (COPD), pneumonia, and heart failure, are among the leading causes of death in the country, especially among the elderly. It is estimated that theseconditions account for around 400,000 deaths annually in Brazil, highlighting their relevance to public health andthe need for continuous preventive actions. To conduct thestudy, a descriptive and quantitative approach wasadopted, based on the analysis of secondary data extractedfrom the Mortality Information System (SIM) of theMinistry of Health and from the statistical panels of theGoiás State Health Department. Records of deaths fromcardiopulmonary diseases between 2022 and 2024 wereconsidered, focusing on the aforementionedmunicipalities. Data were organized into comparativetables and analyzed for temporal variation. In themunicipality of Itapuranga, deaths increased significantly, rising from 13 in 2022 to 37 in 2023. In Uruana andUruíta, however, a reduction was observed: from 29 deaths in 2023 to 23 in 2024, suggesting possible positive effects of local health actions. The results underscore theimportance of effective public policies, focusing onprevention, early diagnosis, and strengthening of primarycare, especially in inland regions.
Keywords: Cardiopulmonary; Diseases; COPD; Mortality; Public Health; Goiás